Intensive Care Unit Admission and Death Rates of Infants Admitted With Respiratory Syncytial Virus Lower Respiratory Tract Infection in Mexico. Issue 11 (November 2016) - Vizcarra-Ugalde, Sergio; Rico-Hernández, Montserrat; Monjarás-Ávila, César; Bernal-Silva, Sofía; Garrocho-Rangel, Maria E.; Ochoa-Pérez, Uciel R.; Noyola, Daniel E.
Abstract : Background: Respiratory syncytial virus (RSV) is the most common etiology for acute respiratory infection hospital admissions in young children. Case fatality rates for hospitalized patients range between 0% and 3.4%. Recent reports indicate that deaths associated with RSV are uncommon in developed countries. However, the role of this virus as a current cause of mortality in other countries requires further examination. Methods: Children with RSV infection admitted between May 2003 and December 2014 to a level 2 specialty hospital in Mexico were included in this analysis. Underlying risk factors, admission to the intensive care unit (ICU) and condition on discharge were assessed to determine the ICU admission and death rates associated to RSV infection. Results: We analyzed data of 1153 patients with RSV infection in whom information regarding underlying illnesses and discharge status was available. Sixty patients (5.2 %) were admitted to the ICU and 12 (1.04 %) died. Relevant underlying conditions were present in 320 (27.7%) patients. Infants with underlying respiratory disorders (excluding asthma) and a history of prematurity had high ICU admission rates (17.1% and 13.8%, respectively). Mortality rates were highest for infants with respiratory disease (excluding asthma) (7.3%), cardiovascular diseases (5.9%) and neurologic disorders (5.3%). The ICU admission and death rates were higher in infants <6 months of age than in other age groups. Conclusions: The ICU admission rate and mortality rate in Mexican infants hospitalized with RSV infection were 5.2% and 1%, respectively. Mortality rates were high in infants with respiratory, cardiovascular and neurologic disorders.